STATE AND PRODUCTIVITY OF OAK STANDS IN FOREST-STEPPE OF KHARKIV REGION - Pyvovar, T. S.; Pasternak, V. P.; Yarotskiy, V. Yu.; Buksha, M. I. (Forestry and Forest Melioration, 2018)
Introduction Oak forests are the dominant forest stands in forest steppe, especially in Kharkiv region. Over the past decade, researchers have noted the degradation and reduction of oak stands in Ukraine. The aim was to study the current state, productivity and biodiversity of oak forests at Forest-Steppe of Kharkiv region at intensive forest monitoring grid. Materials and methods The results of observations at 8 permanent intensive forest monitoring plots at Kharkov region in 2011 and 2015 were analyzed. Plots represent typical oak forests of Left-bank Forest-Steppe, mainly located at moist fertile conditions (7 plots) and moist relatively fertile conditions (1 plot); forest types are fresh maple-lime and maple-ash-lime oakery. Surveyed stands were aged from 69 to 114 years. At monitoring plots, the following characteristics of forest ecosystems components were assessed: stand, regeneration, and dead wood. For data treatment and analysis, computer software applications as GIS Field-Map and LibreOffice 5 were used. Results The largest growing stock is at the oldest oak stand (“Huty”), 411 m3·ha-1, and the lowest is at the oak stand in moist relatively fertile conditions (“Brodok”), 227 m3·ha-1. Current growing stock annual change of studied stands ranges from -0.4 (“Caravan”) to 3.2 (“Huty”), and an average it is 2.1 m3·ha-1·year-1. The negative value of the average change of growing stock is at the plot “Caravan” due to sanitary felling between surveys. The studied stands are generally characterized by a considerable diversity of its composition and complex horizontal and vertical structure. Oak stand on the plot “Neskuchne” is characterized by the highest alpha diversity of tree species by Shannon index (2.08). In terms of standard deviation of tree diameters, the most complex horizontal structure is at plots “Merefa”, “Lyubotin” and “Huty” (99- and 114-year-old stands). The majority of surveyed stands were classified as “healthy” by the average index of sanitary condition (Ic). Only two plots were assessed as “weakend” (“Neskuchne” and “Snizhkiv”). Compared to the previous survey (2011) a significant deterioration at plot “Neskuchne” was stated (Ic increased from 1.37 to 1.61) due to a significant trees dieback, but the condition of living trees has not changed, and the proportion of registered damage is very low. At plot “Brodok”, a significant improvement of health condition was registered (Ic decreases from 1.90 to 1.43) due to the transition of dead trees to laying deadwood. The predominant cause of trees damage in 2015 was the foliage browsing insects. This type of damage was recorded on 7 areas in oak stands, but the intensity of the damage was negligible (within 10 %). Natural regeneration was registered on 7 plots. Regeneration of oak and ash was only at two plots. At other plots, only regeneration of minor woody species as Acer platanoides and A. campestre, Ulmus glabra and Tilia cordata was stated. Dead wood was registered at all plots, but its amount varied from 1.1 to 43.4 m3·ha-1. At “Neskuchne” and “Brodok” plots, the total dead wood stock has significantly increased, while at “Babka”, “Merefa” and “Caravan” plots reduction of deadwood stock was observed. Conclusions The health condition of oak stands on monitoring plots is satisfactory. Compared to 2011, health condition has slightly improved. The predominant cause of trees damage is foliage browsing insects but the damage intensity is relatively low. Studied stands are characterized by considerable diversity by composition and structure (horizontal and vertical). Natural regeneration of the main tree species (oak and ash) was recorded only at two surveyed plots. The current change at growing stock of the stands is relatively low and quite variable (from -0.4 to 3.2) and an average it is 2.1 m3·ha-1 year-1. The stock of dead wood was in general 18.3 m3·ha-1 in 2011 and 16.8 m3·ha-1 in 2015. In most monitoring plots, it has changed slightly between two surveys.